Anabolic steroids: side effects - Kuipers, H. (Sportscience)
Article deals with the following aspects: - Liver Function, - Anabolic Steroids and the Male Reproductive System, - Anabolic Steroids and the Female Reproductive System, - Serum Lipoproteins and the Cardiovascular System, - Psychological Effects, - Additional Side Effects. (Published in: Encyclopedia of Sports Medicine and Science, T.D.Fahey (Editor). Internet Society for Sport Science: http://sportsci.org. 7 March 1998)